Ondansetron enhanced diclofenac‐induced nephrotoxicity in mice. Issue 9 (23rd July 2019) - Shakibaie, Mojtaba; Forootanfar, Hamid; Ghaseminejad, Atoosa; Salimi, Azad; Ameri, Atefeh; Doostmohammadi, Mohsen; Jafari, Elham; Rahimi, Hamid‐Reza
Abstract: This study was performed to investigate the effect of ondansetron, a serotonin receptor (5‐HT3) antagonist, in the alleviation of diclofenac‐induced kidney injuries. NMRI mice were randomly divided into six groups and treated with (A) untreated control group, (B) diclofenac (100 mg/kg), (C) ondansetron (1 mg/kg), (D to F) ondansetron (0.1, 0.5, and 1 mg/kg, respectively) and diclofenac (100 mg/kg) for last 3 days of experiment. The oxidative stress tests strongly demonstrated the negative synergistic effects of diclofenac and ondansetron, regarding the observation of dose‐dependent enhancement of malondialdehyde concentration, and reduction of glutathione content, and superoxide dismutase and catalase activity. Histopathological analyses revealed dose‐dependent tubular epithelial cells degeneration, outstanding mononuclear cells infiltration, clear necrosis at the papillary region of kidney, dilation, and vascular hyperemia in mice kidney tissues treated with ondansetron and diclofenac. Conclusively, these findings suggested the possible ondansetron‐diclofenac interaction through the induction of oxidative stress.